MANAGING ENTREPRENEURSHIP: AN INDONESIAN CONTEXT - ANGGRAENI, ADE IRMA (INDONESIAN RESEARCH SOCIETY, 2019)
Positive values of Western management such as efficiency, discipline and respect for therole of the individual to influence the performance of the organisation. American corporatemanagement practices cannot be separated from values and rationality embraced by thecommunity. Efforts to achieve organisational effectiveness depends on environmentalfactors, one of which cultural factors. Culture is the value system embraced by theenvironment, including the work environment. Based on Hofstede's cultural dimensions, thecollectivist, Indonesia, entrepreneurial management model has the potential to develop thebusiness goals that have value and uniqueness.